Intestinal ischemia following laparoscopic surgery: a case series - Al-Khyatt, Waleed; Thomas, James D.; Humes, David J.; Lobo, Dileep N. (Biomed Central, 2013)
Introduction: Intestinal ischemia is a rare complication of laparoscopic surgery. Its prognosis depends on a high index of suspicion and effective early treatment. Case presentation: In the present report, we describe three cases where intestinal ischemia developed following laparoscopic surgery. Case 1 concerns a 52-year-old Caucasian man who developed large bowel ischemia following laparoscopic adjustable gastric band surgery. Case 2 concerns an 82-year-old Caucasian woman who developed fatal intestinal ischemia following laparoscopic cholecystectomy. Case 3 concerns a 58-year old Caucasian woman who developed right-sided lower intestinal ischemia following open cholecystectomy. Conclusions: Intestinal ischemia is a rare complication of laparoscopic surgery. The identification of high-risk patients is an essential primary preventive measure. A high index of suspicion is required to make an early diagnosis, which may help improve outcomes.